2020
DOI: 10.1021/acs.jpclett.0c03287
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Energy Transfer via Self-Trapped Excitons in Mn2+-Doped 2D Organometal Halide Perovskites

Abstract: We investigate the mechanisms of energy transfer in Mn2+-doped ethylammonium lead bromide (EA2PbBr4:Mn2+), a two-dimensional layered perovskite (2DLP), using cryogenic optical spectroscopy. At temperature T > 120 K, photoluminescence (PL) is dominated by emission from Mn2+, with complete suppression of band edge (BE) emission and self-trapped exciton (STE) emission. However, for T < 120 K, in addition to Mn2+ emission, PL is observed from BE and STEs. Data further reveal that for 20 K < T < 120 K, STEs form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…As shown in Figure a, a characteristic broad emission at 610 nm attributed to the Mn 2+ d–d ( 4 T 1 – 6 A 1 ) transition , was observed, which changed the overall emission color of the solution from purple or deep blue to orange or pink (Figure S4). Mn 2+ dopant emission has been previously observed between 580 and 620 nm in different semiconductors, ,,,,, with variations attributed to differences in the ligand field environment. ,, No absorption feature associated with the dopant state , was observed in our work, presumably due to the low oscillator strength of the spin-forbidden Mn 2+ d–d transition …”
Section: Resultssupporting
confidence: 53%
“…As shown in Figure a, a characteristic broad emission at 610 nm attributed to the Mn 2+ d–d ( 4 T 1 – 6 A 1 ) transition , was observed, which changed the overall emission color of the solution from purple or deep blue to orange or pink (Figure S4). Mn 2+ dopant emission has been previously observed between 580 and 620 nm in different semiconductors, ,,,,, with variations attributed to differences in the ligand field environment. ,, No absorption feature associated with the dopant state , was observed in our work, presumably due to the low oscillator strength of the spin-forbidden Mn 2+ d–d transition …”
Section: Resultssupporting
confidence: 53%
“…Unlike peculiar lead-based 3D bulk perovskites, the band edge PL peak of the Mn 2+ doped EA 2 PbBr 4 perovskite shows a red shi, whereas STE and Mn 2+ emission related peaks suffer from a blue shi with increasing temperature due to enhanced ligand eld strength resulting from the contraction of the octahedra. 112 The red shi of the band edge peak was believed to be a characteristic of single layer perovskites as earlier it was observed in the undoped system also. The bandgap or PL peak shi of 2D perovskites with increasing temperature is dependent on the perovskite layer number as it switches from a blueshi to a redshi from n ¼ N to n ¼ 1, since the bandgap evolution of the semiconductor with temperature is collectively inuenced by the thermal expansion of the lattice resulting in a blue shi and exciton-phonon interaction which has a negative coefficient inducing a red shi.…”
Section: A-site Doping Induced Optoelectronic Propertiesmentioning
confidence: 70%
“… 112 The PL emission intensity of both band edge and STE decreased with increasing T , while that of Mn 2+ concurrently increased, suggesting two pathways of energy transfer: direct energy transfer from the band edge to Mn 2+ and energy transfer to the Mn 2+ band through STEs. 112 Band edge emission completely quenched around 120 K and the activation energy barrier of charge transfer (30–40 meV) from the band edge to Mn 2+ was found to be greater than the thermal energy at low temperature and ambient temperature, which ruled out the possibility of direct energy transfer from the band edge to Mn 2+ dopants. 112 Hence, the main route of energy transfer from the band edge to dopants is followed through STE.…”
Section: Effect Of Doping On the Properties Of 2d Perovskitesmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent investigations show that polaron characteristics may decrease with temperature [16] [17] [18] [19] and a transition from a quantum phase to classical phase predicted [19]. One of the prominent results is seen in ref [20] where the authors investigate experimentally the mechanisms of energy transfer in Mn 2+ doped ethylammonium lead bromide. It is observed that for large temperature, photoluminescence is dominated by emission from Mn 2+ , with a complete suppression of band edge emission and self-trapped exciton emission.…”
Section: Introductionmentioning
confidence: 99%